CART in the regulation of appetite and energy homeostasis - Lau, Jackie; Herzog, Herbert (Frontiers in Neuroscience, 2014)
The cocaine- and amphetamine-regulated transcript (CART) has been the subject of significant interest for over a decade. Work to decipher the detailed mechanism of CART function has been hampered by the lack of specific pharmacological tools like antagonists and the absence of a specific CART receptor(s). However, extensive research has been devoted to elucidate the role of the CART peptide and it is now evident that CART is a key neurotransmitter and hormone involved in the regulation of diverse biological processes, including food intake, maintenance of body weight, reward and addiction, stress response, psychostimulant effects and endocrine functions1,2. In this review, we focus on knowledge gained on CART’s role in controlling appetite and energy homeostasis, and also address certain species differences between rodents and humans.